Analysis Of Factors Affecting The Use Of The Mobile Home Ownership Credit (KPR) Application - Hero Indriyanto*; Muhammad Zarlis (Riwayat: Educational Journal of History and Humanities, 2023)
In its business activities, the Bank has implemented information technology to support various existing business processes. This technology support will change the financial business model to be more efficient and lead to digital services. One form of banking service is the provision of home ownership loans to individual customers who are going to buy or repair a house. PT ABC is a banking company under the auspices of a BUMN that focuses on housing loans. PT ABC has also implemented information technology for the convenience of services that will be provided to consumers. PT ABC has created a mobile mortgage application to facilitate mortgage services to customers. In implementing this mobile mortgage application there are still several obstacles and based on ratings in the Playstore it is still relatively low and there are still negative responses from customers. For this reason, an analysis is needed regarding what factors can support the successful use of this mobile mortgage application where the results of this analysis are expected to later be used as guidelines for improving and optimizing the functions of this application. This study uses a combination of two models, namely UTAUT2 and Delone and Mclean Information Systems which are used to identify the factors that influence the use of the KPR Mobile Application. Data were obtained from 286 respondents who are customers of PT ABC. Then it will be analyzed using SMART PLS software version 3.3.9. The results of this study will later be used for PT ABC as material for evaluating and improving the performance of the KPR mobile application. Based on the results of the research conducted, it is known that Performance expectancy, Social influence, Facilitating conditions, Price value, System quality, Service quality, Information quality have a significant effect on the behavior of using the KPR Mobile application and increasing the use of the KPR Mobile application can positively increase customer satisfaction and increase customer loyalty at PT ABC .